2021
DOI: 10.3389/fpubh.2021.660064
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as a “Digital Push?” Research Experiences From Long-Term Care and Recommendations for the Post-pandemic Era

Abstract: BACKGROUNDHealth authorities and governments worldwide label older adults as a "risk group" for more serious and possibly fatal illness associated with SARS-CoV-2 (COVID-19) (1). Those older adults living in long-term care (LTC) are considered especially prone to more serious and fatal disease following a COVID-19 infection (2). Consequently, measures requiring LTC residents to shelter in place and maintain physical distancing from others have been enacted in many countries during the pandemic. However, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…A previous study conducted by Harvard and MIT between 2012 and 2014 reported that MOOC participants tended to live in more affluent and better-educated neighborhoods than the average U.S. resident ( 20 ). Studies have also reported that telemedicine could be helpful in the current pandemic, but organizational readiness to adopt telemedicine needs urgent attention ( 24 , 26 ). Does digital divide exist despite broad accessibility of mobile tools and internet use in China?…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted by Harvard and MIT between 2012 and 2014 reported that MOOC participants tended to live in more affluent and better-educated neighborhoods than the average U.S. resident ( 20 ). Studies have also reported that telemedicine could be helpful in the current pandemic, but organizational readiness to adopt telemedicine needs urgent attention ( 24 , 26 ). Does digital divide exist despite broad accessibility of mobile tools and internet use in China?…”
Section: Discussionmentioning
confidence: 99%
“…The onset of COVID-19 and the ensuing social distancing policies have led to a burgeoning interest in technology-based solutions, including digital devices such as tablets, wearable devices, and digital communication platforms to provide care and promote health [ 1 ]. Indeed, during the COVID-19 pandemic, several digital technologies have been adopted as alternatives to face-to-face communication [ 2 ]. To reduce loneliness and social isolation, many long-term care facilities have provided technologies such as Skype, FaceTime, and Zoom to allow residents to interact digitally with their relatives [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Future research should explore further the differences between different modes of delivery to provide more options for multiple participants with varying levels of capacity, abilities, and resources in unique rural contexts, including microlevel interactions. Interactive ICT initiatives will be effective in engaging meaningful social engagement when they can be responsive and adaptive to unique contexts by incorporating feedback channels, training and support for local facilitation; participation with different stakeholders; and adequate devices and internet ( Gallistl et al, 2021 ; Hennesy & Innes, 2020 ; Van der Heide et al, 2012 ). In light of the COVID-19 pandemic and the rush to digital solutions, and as communities consider whether internet access should be a basic human right, careful consideration should be taken as to the necessary skills development and support required for diverse stakeholders, alongside the provision of infrastructure and devices ( Seifert et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This presented a myriad of challenges for multiple stakeholders in a variety of settings and processes. Researchers in the field as well as service providers and practitioners thus need to be aware that the use of ICT in addressing social needs is a complex process involving many actors ( Gallistl et al, 2021 ). Many older adults require support to remain engaged in ICT environments and have concerns about complicated processes and undue burden that can lead to social isolation ( Innovation, Science and Economic Development Canada, 2019 ).…”
Section: Background and Objectivesmentioning
confidence: 99%